DNA functionalization of colloidal particles via physisorption of azide-functionalized diblock copolymers. Issue 35 (2nd August 2019) - Moon, Jeongbin; Jo, In-Seong; Yoon, Jeong Hoon; Kim, Yeongha; Oh, Joon Suk; Pine, David J.; Yi, Gi-Ra
Abstract : DNA-coated colloids are prepared simply by physical adsorption of azide-functionalized amphiphilic diblock copolymers onto hydrophobic inorganic particles, followed by strain-promoted azide–alkyne cycloaddition (SPAAC) reaction. Abstract : DNA-coated inorganic particles can be prepared simply by physical adsorption of azide-functionalized diblock copolymers (polystyrene- b -poly(ethylene oxide)-azide, PS- b -PEO-N3 ) onto hydrophobically-modified inorganic particles, followed by strain-promoted azide–alkyne cycloaddition (SPAAC, copper-free click chemistry). This approach is applied to organosilica, silica and titania particles. The DNA-coated colloids are successfully crystallized into colloidal superstructures by a thermal annealing process using DNA-mediated assembly.